Corticospinal excitability modulation by pairing peripheral nerve stimulation with cortical states of movement initiation. (2nd November 2019) - Fu, Lingdi; Rocchi, Lorenzo; Hannah, Ricci; Xu, Guizhi; Rothwell, John C.; Ibáñez, Jaime
Abstract : Key points: We compare the effects on corticospinal excitability of repeatedly delivering peripheral nerve stimulation at three time points (−30 ms, 0 ms, +50 ms) relative to muscle onset in a cue‐guided task. Plastic changes in excitability are only observed when stimuli are delivered immediately before the time when muscles activate, while stimuli delivered at muscle onset or shortly later (0, +50 ms) have no effect. Plastic effects are abolished if there is ongoing volitional electromyogram activity in the muscles prior to the onset of the phasic contraction. The plastic effects induced by timing peripheral stimulation relative to electromyographic markers of muscle activation are as effective as those that occur if stimulation is timed relative to electroencephalographic markers of motor cortical activation. We provide a simple alternative protocol to induce plasticity in people in whom electroencephalogram recording is difficult. Abstract: Plastic changes in corticospinal excitability (CSE) and motor function can be induced in a targeted and long‐term manner if afferent volleys evoked by peripheral nerve stimulation are repeatedly associated with the peak of premovement brain activity assessed with an electroencephalogram (EEG). The present study investigated whether other factors might also characterize this optimal brain state for plasticity induction. In healthy human volunteers ( n  = 24), we found that the same reliable changes in CSE can be induced by timing peripheral afferent stimulation relative to the onset of electromyogram (EMG) activity rather than using the EEG peak. Specifically, we observed an increase in CSE when peripheral stimulation activated the cortex just before movement initiation. By contrast, there was no effect on CSE if the afferent input reached the cortex at the same time or after EMG onset, consistent with the idea that the temporal order of synaptic activation from afferent input and voluntary movement is important for production of plasticity. Finally, in 14 volunteers, we found that background voluntary muscle activity prior to movement also abolished the effect on CSE. One possible explanation is that the intervention strengthens synapses that are inactive at rest but change their activity in anticipation of movement, and that the intervention fails when the synapses are tonically active during background EMG activity. Overall, we demonstrate that, in individuals with voluntary control of muscles targeted by our intervention, EMG signals are a suitable alternative to an EEG for inducing plasticity by coupling movement‐related brain states with peripheral afferent input. Key points: We compare the effects on corticospinal excitability of repeatedly delivering peripheral nerve stimulation at three time points (−30 ms, 0 ms, +50 ms) relative to muscle onset in a cue‐guided task. Plastic changes in excitability are only observed when stimuli are delivered immediately before the time when muscles activate, while stimuli delivered at muscle onset or shortly later (0, +50 ms) have no effect. Plastic effects are abolished if there is ongoing volitional electromyogram activity in the muscles prior to the onset of the phasic contraction. The plastic effects induced by timing peripheral stimulation relative to electromyographic markers of muscle activation are as effective as those that occur if stimulation is timed relative to electroencephalographic markers of motor cortical activation. We provide a simple alternative protocol to induce plasticity in people in whom electroencephalogram recording is difficult.